A novel endoscopic submucosal dissection technique with robust and adjustable tissue traction - Hirota, Masashi; Kato, Motohiko; Yamasaki, Makoto; Kawai, Naoki; Miyazaki, Yasuhiro; Yamada, Takuya; Takahashi, Tsuyoshi; Takehara, Tetsuo; Mori, Masaki; Doki, Yuichiro; Nakajima, Kiyokazu (Endoscopy, 2014)
Background and study aims: A novel esophageal endoscopic submucosal dissection (ESD) technique was devised using a newly developed overtube to achieve adequate tissue traction. The aim of this study was to evaluate the feasibility and safety of this new full-traction ESD (tESD) technique.Methods: The key feature of tESD is tissue traction by grasping forceps, which is passed through the built-in side channel of the overtube. The strength and direction of traction is controlled by rotating the overtube and by adjusting its depth. The en bloc resection rate, procedure time, adverse events, and dissected area per minute were evaluated in a porcine model (n = 10) and compared with those of conventional ESD (n = 10).Results: tESD provided robust and adjustable tissue traction during the procedure. En bloc resection was accomplished in all lesions with no complications. Median procedure time was similar to that of the conventional technique (25 vs. 27 minutes; P = 0.4723) but the submucosal injection catheter was used less often (1.5 vs. 6; P < 0.01). Conclusions: tESD might contribute to more efficient esophageal ESD by providing adequate tissue traction. This inexpensive technique may become an attractive option in esophageal ESD.